Union Responses to Workplace COVID-19 Vaccine Mandates in Canada - Braley-Rattai, Alison; Savage, Larry (Labour / Le Travail)

(untitled) (Canadian Committee on Labour History, 2024)
This article explores union responses to workplace-based covid-19 vaccine mandates in Canada. Specifically, the authors examine the complex interplay of factors that drove unions to adopt their respective positions on vaccine mandates and to frame those positions in particular ways for the benefit of their members and the wider public. Interviews with key informants, along with analysis of documents and arbitration decisions, reveal a disjuncture between the discursive quality of certain unions’ positions and their actual positions. In particular, media framing of unions as either “for” or “against” vaccine mandates oversimplified or misrepresented the actual positions adopted. In response, the article introduces a typology of union positions that distinguishes between support for mandatory-vaccination policies and support for voluntary-vaccination policies and reveals that the vast majority of unions favoured the latter. The authors further reveal that workplace vaccine mandates were both internally divisive and disorienting for unions, given the central role labour organizations play in managing workplace disputes and representing the interests of workers, both individually and collectively.